Application of Iron Aluminides in the Combustion Chamber of Large Bore 2-Stroke Marine Engines - Frank Moszner; Jian Peng; Jyrki Suutala; Ulf Jasnau; Monika Damani; Martin Palm (Metals, 2019)
Iron aluminides possess a unique combination of properties such as attractive corrosion resistance in hot gas and wet chemical environments, a favorable strength to weight ratio, low costs of alloying elements, and they can be processed by conventional methods. For the current study, a promising iron aluminide (Fe-Al-Mo-Ti-B) was employed, which shows the potential to replace costly heat resistant steels or expensive Ni-based alloys for components in large bore two-stroke marine engines. The prechamber, an integral part of the combustion system of dual fuel two-stroke marine engines, which must withstand harsh conditions, was selected as the component. Prototypes made of the novel iron aluminide were manufactured via investment casting and hot isostatic pressing using powder of the intermetallic alloy. The high temperature oxidation behavior, the wet corrosion resistance in acid media, and the mechanical properties up to 700 °C were evaluated. A prototype of the prechamber was tested on a large bore two-stroke dual fuel test engine and post analysis of the tested component was performed. The results show that the employed iron aluminide alloy could be an economic alternative to the currently used Ni-based alloy.